Vectorial Capacity of Culiseta melanura (Diptera: Culicidae) Changes Seasonally and Is Related to Epizootic Transmission of Eastern Equine Encephalitis Virus in Central Florida - West, Richard G.; Mathias, Derrick R.; Day, Jonathan F.; Boohene, Carl K.; Unnasch, Thomas R.; Burkett-Cadena, Nathan D. (Frontiers in Ecology and Evolution, 2020)
Vectorial capacity is an equation that integrates major aspects of vector biology to predict the number of new mosquito-borne disease infections. Developed for studying transmission of malaria, vectorial capacity is rarely applied to zoonotic vector-borne diseases and is not often adjusted to account for seasonal changes in vector ecology. We used field data from Florida, USA to expand the understanding of how vectorial capacity of Culiseta melanura (Coquillett), the primary enzootic vector of eastern equine encephalitis virus (EEEV), changes seasonally and its effect on EEEV risk. We determined parity via dissection and identified bloodmeals by PCR for field-collected Cs. melanura females from central Florida. We used density of the vector, proportion of avian hosts fed upon, parity state of the vector, and mean temperature of the study area to quantify vectorial capacity as a function of season. The calculated values of vectorial capacity shifted significantly with season, with highest values observed in the summer with an additional peak in December. Linear regression revealed a strong positive correlation between vectorial capacity values and Florida EEEV equine cases in 2018, as well as cases reported during the last decade. The relationship between virus infections in equids and vectorial capacity lends support to the large effect that enzootic transmission has on epizootic outbreaks of zoonotic vector-borne pathogens.